2020
DOI: 10.1002/14651858.cd011961.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive training interventions for dementia and mild cognitive impairment in Parkinson’s disease

Abstract: What we foundCognitive training interventions for dementia and mild cognitive impairment in Parkinson's disease (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 166 publications
(50 reference statements)
7
73
1
2
Order By: Relevance
“…Two meta-analyses have demonstrated CT benefits in PD patients, particularly with respect to executive functions, working memory, memory, and processing speed [9,10]. However, a recent Cochrane review and metaanalysis [11] found that studies on CT in PD patients so far do not give evidence for "important cognitive improvements." e authors point out that reliable conclusions cannot be drawn yet due to a small number of studies with few participants, limitations of study design and execution, and imprecise results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two meta-analyses have demonstrated CT benefits in PD patients, particularly with respect to executive functions, working memory, memory, and processing speed [9,10]. However, a recent Cochrane review and metaanalysis [11] found that studies on CT in PD patients so far do not give evidence for "important cognitive improvements." e authors point out that reliable conclusions cannot be drawn yet due to a small number of studies with few participants, limitations of study design and execution, and imprecise results.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in CT studies, the patients' cognitive status has only rarely been assessed based on established criteria. erefore, its efficacy in PD, PD-MCI, and PD dementia (PDD) cannot be derived [11,12]. Also, noncognitive outcomes (e.g., quality of life and neuropsychiatric symptoms) have only scarcely been examined in existing randomized controlled trials (RCTs) [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is more likely that individuals early in the disease will have a more responsive striatal system. Also, a recent meta-analysis from the Cochrane Library found no evidence for any important cognitive improvement after 4 to 8 weeks of cognitive training in PD-MCI and PDD [53]. This indicates that cognitive interventions might be more suitable early in the disease when the cognitive decline is less pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several systematic reviews and meta-analyses have investigated the efficacy of cognitive training on cognitive function in PD. [5][6][7][8] Leung and colleagues identified seven randomised controlled trials (RCTs) and concluded that cognitive training showed modest efficacy for overall cognition in PD, with larger effect sizes observed within individual cognitive domains. 5 Similar results were reported by Lawrence and colleagues, 6 who combined 11 randomised and non-randomised cognitive training trials.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a Cochrane review identified seven RCTs investigating the effects of cognitive training in patients with PD with MCI or dementia, reporting imprecise and uncertain evidence for efficacy on global cognition. 7 Approaches for estimating effect sizes across studies varied across reviews, and none conducted investigations of heterogeneity. Finally, a recent systematic review focusing specifically on CCT reported evidence for cognitive benefits based on seven RCTs; however, no meta-analysis was performed and potential effect modifiers were not explored.…”
Section: Introductionmentioning
confidence: 99%